2012
DOI: 10.1007/s10658-012-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Verticillium dahliae through watering systems in widely irrigated olive growing areas in Andalucia (southern Spain)

Abstract: Verticillium dahliae Kleb. causes Verticillium wilts in many herbaceous and woody species. Many hosts of the pathogen are commonly cultivated in Andalucía (southern Spain), particularly major crops such as cotton, vegetables, almond, peach and, particularly, olive, in which the fungus causes Verticillium wilt of olive. Infective structures of the pathogen (microsclerotia), produced in the late phases of the infection cycle in senescent tissues of the infected plants, can be spread over short or long distances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Irrigation waters in Andalusian olive orchards can harbour and disperse V. dahliae propagules (Rodríguez‐Jurado & Bejarano‐Alcázar, ; García‐Cabello et al ., ), particularly those of the highly virulent, defoliating V. dahliae pathotype, which frequently causes death of the Picual cultivar (Jiménez‐Díaz et al ., ; Moraño‐Moreno et al ., ). This cultivar is one of the most economically (and historically) important in Spain (López‐Escudero & Mercado‐Blanco, ) and this could explain why it is still used in Andalusia instead of resistant cultivars, which are available (Rodríguez‐Jurado et al ., ; López‐Escudero et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation waters in Andalusian olive orchards can harbour and disperse V. dahliae propagules (Rodríguez‐Jurado & Bejarano‐Alcázar, ; García‐Cabello et al ., ), particularly those of the highly virulent, defoliating V. dahliae pathotype, which frequently causes death of the Picual cultivar (Jiménez‐Díaz et al ., ; Moraño‐Moreno et al ., ). This cultivar is one of the most economically (and historically) important in Spain (López‐Escudero & Mercado‐Blanco, ) and this could explain why it is still used in Andalusia instead of resistant cultivars, which are available (Rodríguez‐Jurado et al ., ; López‐Escudero et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Contaminated water of irrigation systems, especially in wide cultivation areas, can disperse the pathogen's propagules (Rodriguez-Jurado and Bejarano-Alcazar, 2007;Garcia-Cabello et al, 2012). This dispersal of V. dahliae propagules by contaminated irrigation water has been demonstrated in several herbaceous crops (Easton et al, 1969).…”
Section: Spread By Human Assistancementioning
confidence: 98%
“…The installation of filtration systems is a widespread practice aimed at preventing the clogging of drippers. It has been demonstrated that commercial sand filters fail to prevent V. dahliae spread through drip‐irrigation systems of Andalusian olive orchards (García‐Cabello et al ., ). On the other hand, treating V. dahliae ‐infested water with some disinfectants, namely OX‐VIRIN and OX‐AGUA AL25, reported potential efficacy in reducing the propagules of the fungus, which was enhanced by increasing both the exposure time and the concentration of the product.…”
Section: Introductionmentioning
confidence: 97%
“…García‐Cabello et al . () demonstrated that the pathogen was capable of surviving and dispersing as viable sclerotia when moved medium and long distances from a pumping station to research plots. Furthermore, Rodríguez‐Jurado et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation